Optimization of the surgical treatment of optic neuropathy in patients with myopia high degree - O. O. Denisova (Zaporožskij Medicinskij Žurnal)
Aim. There was made a comparative assessment of treatment efficiency in patients with myopia of high degree who have manifestations of an optical neuropathy.